Celecoxib Prevents Cognitive Impairment and Neuroinflammation in Soluble Amyloid β-treated Rats. (21st February 2018) - Mhillaj, Emanuela; Morgese, Maria Grazia; Tucci, Paolo; Furiano, Anna; Luongo, Livio; Bove, Maria; Maione, Sabatino; Cuomo, Vincenzo; Schiavone, Stefania; Trabace, Luigia
Highlights: Celecoxib reverts cognitive impairment induced by sAβ. Celecoxib prevents neuroinflammation induced by sAβ. Celecoxib might result as potential remedy counterbalancing sAβ-induced effects. Abstract: Recent findings suggest that soluble forms of amyloid-β (sAβ) peptide contribute to synaptic and cognitive dysfunctions in early stages of Alzheimer's disease (AD). On the other hand, neuroinflammation and cyclooxygenase-2 (COX-2) enzyme have gained increased interest as key factors involved early in AD, although the signaling pathways and pathophysiologic mechanisms underlying a link between sAβ-induced neurotoxicity and inflammation are still unclear. Here, we investigated the effects of selective COX-2 enzyme inhibition on neuropathological alterations induced by sAβ administration in rats. To this purpose, animals received an intracerebroventricular (icv) injection of predominantly monomeric forms of sAβ and, 7 days after, behavioral as well as biochemical parameters and neurotransmitter alterations were evaluated. During this period, rats also received a sub-chronic treatment with celecoxib. Biochemical results demonstrated that icv sAβ injection significantly increased both COX-2 and pro-inflammatory cytokines expression in the hippocampus (Hipp) of treated rats. In addition, the number of hypertrophic microglial cells and astrocytes were upregulated in sAβ-treated group. Interestingly, rats treated with sAβ showed long-term memory deficits, as confirmed by a significant reduction of discrimination index in the novel object recognition test, along with reduced brain-derived neurotrophic factor expression and increased noradrenaline levels in the Hipp. Systemic administration of celecoxib prevented behavioral dysfunctions, as well as biochemical and neurotransmitter alterations. In conclusion, our results suggest that sAβ neurotoxicity might be associated to COX-2-mediated inflammatory pathways and that early treatment with selective COX-2 inhibitor might provide potential remedies to counterbalance the sAβ-induced effects.